2021
DOI: 10.3390/molecules26164933
|View full text |Cite
|
Sign up to set email alerts
|

Can Eucalyptol Replace Antibiotics?

Abstract: One of the primary reasons for the search for new antimicrobial agents is the increasing and spreading resistance of microorganisms to previously used drugs. This is particularly important in the case of rapidly progressing infections that require the rapid administration of an appropriately selected antibiotic. However, along with the administration of antibiotics, complications in the disease-weakened body may arise in the form of systemic mycoses, viral infections, and protozoan infections. Therefore, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 86 publications
1
30
0
1
Order By: Relevance
“…Most importantly, several naphthalene containing drugs with a broad spectrum of biological activities are approved by the FDA and are available as therapeutics [ 47 ]. Closely, eucalyptol has been latterly proposed as an excellent natural replacer for antibiotics due to its powerful bactericidal activity against a wide range of potential pathogenic Gram (+) and Gram (−) bacteria [ 49 ]. Moreover, eucalyptol has also shown remarkable synergistic interaction with traditional antibiotics such as amoxicillin and gentamicin, suggesting its combination therapeutic benefit in cases of MDR and mixed-bacterial infections [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, several naphthalene containing drugs with a broad spectrum of biological activities are approved by the FDA and are available as therapeutics [ 47 ]. Closely, eucalyptol has been latterly proposed as an excellent natural replacer for antibiotics due to its powerful bactericidal activity against a wide range of potential pathogenic Gram (+) and Gram (−) bacteria [ 49 ]. Moreover, eucalyptol has also shown remarkable synergistic interaction with traditional antibiotics such as amoxicillin and gentamicin, suggesting its combination therapeutic benefit in cases of MDR and mixed-bacterial infections [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major ingredients of the Eucalyptus leaf oil is 1,8-cineole (Eucalyptol). It is a cyclic ether with an empirical formula C 10 H 18 O. Eucalyptol determines the commercial value of Eucalyptus essential oil for various industries [71]. Recent studies have demonstrated the tremendous potential of Eucalyptol and its antimicrobial properties (reviewed in [71]).…”
Section: Factors Influencing the Essential Oil Composition Of Plantsmentioning
confidence: 99%
“…It is a cyclic ether with an empirical formula C 10 H 18 O. Eucalyptol determines the commercial value of Eucalyptus essential oil for various industries [71]. Recent studies have demonstrated the tremendous potential of Eucalyptol and its antimicrobial properties (reviewed in [71]). It's percent and antibacterial activity depends on the specific species [1,19].…”
Section: Factors Influencing the Essential Oil Composition Of Plantsmentioning
confidence: 99%
“…Eucalyptol (1,8-Cineole) is known for its strong antimicrobial activity, and it might be an excellent alternative to synthetic drugs in the treatment of diseases, including infectious diseases [ 79 ]. Aldoghaim et al determined the antimicrobial activity of the EOs from several west Australian species of Eucalyptus [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eucalyptol (1,8-Cineole) is known for its strong antimicrobial activity, and it might be an excellent alternative to synthetic drugs in the treatment of diseases, including infectious diseases [79]. Aldoghaim The Eucalyptus EOs showed variable antimicrobial activity against the different microorganisms tested with the MIC values ranging from 0.25% to 8.0% (v/v) determined by the broth microdilution assay.…”
Section: Antimicrobial Activitymentioning
confidence: 99%